2012
DOI: 10.1152/ajpheart.00338.2012
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in ESC differentiation

Abstract: MicroRNAs (miRNAs) are small sequences of noncoding RNAs that regulate gene expression by two basic processes: direct degradation of mRNA and translation inhibition. miRNAs are key molecules in gene regulation for embryonic stem cells, since they are able to repress target pluripotent mRNA genes, including Oct4, Sox2, and Nanog. miRNAs are unlike other small noncoding RNAs in their biogenesis, since they derive from precursors that fold back to form a distinctive hairpin structure, whereas other classes of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 69 publications
0
34
0
2
Order By: Relevance
“…The G1/S transition is regulated by the cyclin D-Cdk4, 6 and cyclin E-Cdk2 complexes. The cyclin D-Cdk4, 6 complex is not present in mouse ESCs; however, the cyclin E-Cdk2 complex that induces S phase and DNA replication is present and active [20,37] . In vivo experiments performed in a developing lung demonstrated that miR-302-367 decreased the expression of inhibitors of cdkn1a (p21) and Rbl2, inhibitors of the cyclin E-Cdk2 complex, which resulted in the formation of an undifferentiated multi-layered lung endoderm [38] .…”
Section: Micrornas In Maintenancementioning
confidence: 97%
See 1 more Smart Citation
“…The G1/S transition is regulated by the cyclin D-Cdk4, 6 and cyclin E-Cdk2 complexes. The cyclin D-Cdk4, 6 complex is not present in mouse ESCs; however, the cyclin E-Cdk2 complex that induces S phase and DNA replication is present and active [20,37] . In vivo experiments performed in a developing lung demonstrated that miR-302-367 decreased the expression of inhibitors of cdkn1a (p21) and Rbl2, inhibitors of the cyclin E-Cdk2 complex, which resulted in the formation of an undifferentiated multi-layered lung endoderm [38] .…”
Section: Micrornas In Maintenancementioning
confidence: 97%
“…Interestingly, the first two miRNAs discovered, lin-4 and let-7, were characterized during the developmental stage transition in C. elegans [16,17] . By deleting enzymes involved in miRNA processing and maturation, namely, Dicer or Dgcr8, studies have shown that miRNAs are important in maintaining ESC pluripotency and differentiation capacity [18][19][20] . miRNAs also play a role in the differentiation and self-renewal of mesenchymal stem cells (MSCs) [21] .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have been shown to be essential for ESC differentiation, and a number have been shown to be directly involved in the directed differentiation of ESCs to specific lineages. 14 An RNAi screen set out to identify novel regulators of ESC self-renewal identified a wide selection of mRNAs that when knocked down, induce ESCs to differentiate. Interestingly, a significant number of these were RNA regulators, implicating post-transcriptional control in selfrenewal and differentiation.…”
Section: A Role For Polyamine Regulators In Esc Self-renewalmentioning
confidence: 99%
“…For example, aberrant methylation in cancer is frequently observed 6 and the distinct patterns of promoter methylation between monozygotic (MZ) twin pairs have also been found to result in different health conditions 7 . In contrast to DNA methylation, miRNA regulation of target genes is more flexible and can change even during cellular differentiation 8 . miRNA expression is often tissue-specific, and similar to DNA methylation, miRNA expression has been linked to human disease 9 .…”
Section: Introductionmentioning
confidence: 99%